Behçet's syndrome presenting as myocardial infarction with impaired blood fibrinolysis. - Hutchison, S J (1984)
A 34 year old man with no known coronary risk factors presented with acute myocardial infarction. Shortly after admission, and over the next eight years, he had recurring clinical features consistent with a diagnosis of Behçet's syndrome. Coronary angiograms recorded six months after infarction were normal. Although he was well with maintenance steroid treatment, blood fibrinolysis was impaired. Myocardial infarction has not previously been reported as a presenting feature of the syndrome.